Flexible spiral bicycle wheel / Muhammad Salahuddin Ayubi Rosnelizaide ... [et al.] - Rosnelizaide, Muhammad Salahuddin Ayubi; Mohammad Adrus, Nur Adilah Aina; Mohammad Fauzi, Farisya Irdina; Zainuddin, Nurul Ain (2024)
Bicycles are the greatest invention of all humankind. It helps man to transport everywhere by using their own energy. A bicycle is a two-wheeled vehicle that cyclists sit on and move by turning the two pedals. Unfortunately, even though each bicycle wheel comes with a tough rubber tire, not all cyclists feel comfortable over terrains. To provide more comfort when confronting multiple surfaces, bicycle wheels should be altered to make them function like a suspension while maintaining grips. The universality of the altered bicycle wheels is also important as it can be used by different types of bicycles. Through delving deep into information research, simulations and understanding videos about bicycle physics and concepts, the result led to the possibility of adjusting the wheels to unique features as it provides support for the frame and is able to work like the original bicycle wheel. Overall, the comfort of bicycle riding is important to cyclists to experience optimum riding experience and a healthy life. With the innovation of ‘Flexible Spiral Bicycle Wheel,’ the existing suspension in the wheel can attract more customers to only purchase the wheels.